Genomic epidemiology of SARS-CoV-2 transmission lineages in Ecuador. Issue 2 (4th June 2021) - Gutierrez, Bernardo; Márquez, Sully; Prado-Vivar, Belén; Becerra-Wong, Mónica; Guadalupe, Juan José; Candido, Darlan Da Silva; Fernandez-Cadena, Juan Carlos; Morey-Leon, Gabriel; Armas-Gonzalez, Rubén; Andrade-Molina, Derly Madeleiny; Bruno, Alfredo; De Mora, Domenica; et al.
Abstract: Characterisation of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) genetic diversity through space and time can reveal trends in virus importation and domestic circulation and permit the exploration of questions regarding the early transmission dynamics. Here, we present a detailed description of SARS-CoV-2 genomic epidemiology in Ecuador, one of the hardest hit countries during the early stages of the coronavirus-19 pandemic. We generated and analysed 160 whole genome sequences sampled from all provinces of Ecuador in 2020. Molecular clock and phylogeographic analysis of these sequences in the context of global SARS-CoV-2 diversity enable us to identify and characterise individual transmission lineages within Ecuador, explore their spatiotemporal distributions, and consider their introduction and domestic circulation. Our results reveal a pattern of multiple international importations across the country, with apparent differences between key provinces. Transmission lineages were mostly introduced before the implementation of non-pharmaceutical interventions, with differential degrees of persistence and national dissemination.